2002
DOI: 10.1029/2002gl015190
|View full text |Cite
|
Sign up to set email alerts
|

Nitric acid concentrations near the tropical tropopause: Implications for the properties of tropical nitric acid trihydrate clouds

Abstract: [1] In situ measurements of NO y , NO x , and temperature confirm that nitric acid trihydrate (NAT) particles could form at the tropical tropopause. The HNO 3 mixing ratio near the tropical tropopause is typically no larger than about 0.2-0.3 ppbv, and the corresponding equilibrium mass of nitric acid trihydrate (NAT) is no larger than 0.3 mg m À3. Considerably larger NAT condensed masses are required to explain the HALOE extinctions; however, localized regions of enhanced HNO 3 produced by oxidation of lightn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…They concluded that a subset of the clouds that were depolarizing and had color ratios significantly less than unity were possibly Nitric Acid Trihydrate (NAT) particles. This conclusion is implausible because the nitric acid concentration in the TTL is far too low to produce NAT clouds detectable by CALIPSO (Jensen and Drdla, 2002;Poole et al, 2009). What the CALIOP measurements do suggest is that some fraction of TTL clouds are composed of small (a few microns or less), nonspherical particles.…”
Section: Ice Crystal Concentrationsmentioning
confidence: 75%
“…They concluded that a subset of the clouds that were depolarizing and had color ratios significantly less than unity were possibly Nitric Acid Trihydrate (NAT) particles. This conclusion is implausible because the nitric acid concentration in the TTL is far too low to produce NAT clouds detectable by CALIPSO (Jensen and Drdla, 2002;Poole et al, 2009). What the CALIOP measurements do suggest is that some fraction of TTL clouds are composed of small (a few microns or less), nonspherical particles.…”
Section: Ice Crystal Concentrationsmentioning
confidence: 75%
“…Thus, for an airmass to form an amount of NAT corresponding to 0.13-2.3 ppbv, it would require an unexplained abnormally high HNO 3 abundance during the nucleation and growth of NAT particles. Jensen and Drdla (2002) have reported localized regions with higher concentration of HNO 3 at the tropical tropopause. It cannot be ruled out that the HNO 3 concentration may be enhanced sufficiently to produce NAT above convective areas, due to flash induced NO x formation in convective systems, but it is not necessary to assume that the particles were composed of NAT in order to explain their occurrence.…”
Section: Number Density and Compositionmentioning
confidence: 99%
“…However, from the CVI-TDL (Counterflow Virtual-Impactor -Tunable Diode Laser, detection limit ≈0.2 ppb) measurements onboard Geophysica during the APE-THESEO campaign there is no evidence for HNO 3 in the particles (see Luo et al, 2003). The measurements made on ER-2 flights in the tropics show a HNO 3 mixing ratio typically 0.1-0.5 ppbv (Jensen and Drdla, 2002), which is too low to explain either the HALOE extinctions (Jensen and Drdla, 2002) or the UTTCs. Furthermore, a detailed investigation of the UTTC lidar data reveals that evidence for a distinct difference between ice clouds and HNO 3 -hydrate clouds, as known from lidar measurements in the polar regions (Type-1 versus Type-2 polar stratospheric clouds), is missing.…”
Section: The Uttc Paradoxmentioning
confidence: 99%